2017
DOI: 10.1124/dmd.117.078048
|View full text |Cite
|
Sign up to set email alerts
|

The JAK1/2 Inhibitor Ruxolitinib Reverses Interleukin-6-Mediated Suppression of Drug-Detoxifying Proteins in Cultured Human Hepatocytes

Abstract: The inflammatory cytokine interleukin (IL)-6, which basically activates the Janus kinase (JAK)/ signal transducer and activator of transcription (STAT) signaling pathway, is well known to repress expression of hepatic cytochromes P-450 (P450s) and transporters. Therapeutic proteins, like monoclonal antibodies targeting IL-6 or its receptor, have consequently been demonstrated to restore full hepatic detoxification capacity, which results in inflammatory disease-related drug-drug interactions (idDDIs). In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 56 publications
(67 reference statements)
1
27
0
Order By: Relevance
“…However, such strategies are rarely implemented and reported studies often fail to include positive and negative control inhibitors into the experimental design, which is recommended in the regulatory guidance documents. These issues complicate the interpretation of data and can result in discrepant views on extrapolating from in vitro studies to the clinical situation, as reported for ruxolitinib or crizotinib, where experimental data would suggest statistically significant but not clinically relevant degrees of inhibition [ 67 , 68 , 69 ]. Substrate selection: Since substrate-dependent inhibition by xenobiotics, including TKIs, has been well documented and is acknowledged expressly in the FDA guidance document, the degree to which findings obtained with one particular substrate can be extrapolated to other conditions is uncertain, and potentially accounts for several reported inconsistencies.…”
Section: Effects Of Tkis On the Function Of Oatp1b1 And Oatp1b3mentioning
confidence: 99%
See 1 more Smart Citation
“…However, such strategies are rarely implemented and reported studies often fail to include positive and negative control inhibitors into the experimental design, which is recommended in the regulatory guidance documents. These issues complicate the interpretation of data and can result in discrepant views on extrapolating from in vitro studies to the clinical situation, as reported for ruxolitinib or crizotinib, where experimental data would suggest statistically significant but not clinically relevant degrees of inhibition [ 67 , 68 , 69 ]. Substrate selection: Since substrate-dependent inhibition by xenobiotics, including TKIs, has been well documented and is acknowledged expressly in the FDA guidance document, the degree to which findings obtained with one particular substrate can be extrapolated to other conditions is uncertain, and potentially accounts for several reported inconsistencies.…”
Section: Effects Of Tkis On the Function Of Oatp1b1 And Oatp1b3mentioning
confidence: 99%
“…However, such strategies are rarely implemented and reported studies often fail to include positive and negative control inhibitors into the experimental design, which is recommended in the regulatory guidance documents. These issues complicate the interpretation of data and can result in discrepant views on extrapolating from in vitro studies to the clinical situation, as reported for ruxolitinib or crizotinib, where experimental data would suggest statistically significant but not clinically relevant degrees of inhibition [ 67 , 68 , 69 ].…”
Section: Effects Of Tkis On the Function Of Oatp1b1 And Oatp1b3mentioning
confidence: 99%
“…UMR106 cells were plated in 96-well tissue culture plates (5 Â 10 4 cells/well) and incubated with HIL-6 (100 ng/ml) 37 or vehicle (0.1% bovine serum albumin). Ruxolitinib (5 mmol/l in ethanol) (Cayman Chemical Company, Ann Arbor, MI) 52 was added without or with HIL-6. HeLa cells in 96-well plates at 80% to 90% confluency were transfected transiently using Lipofectamine 3000 (Invitrogen, Carlsbad, CA).…”
Section: Calvaria Organ Culturesmentioning
confidence: 99%
“…HGF treatment was next demonstrated to concomitantly induce ENT1 activity (Figure 9D). Finally, the Janus kinase (JAK) inhibitor ruxolitinib, which has previously been shown to reverse IL6-mediated suppression of the hepatic sinusoidal drug transporters sodium-taurocholate cotransporting polypeptide (NTCP/ SLC10A1 ), OATP1B1 and OCT1 [37], also hindered IL6-mediated down-regulation of CNT1 (Figure 9E) and ENT2 (Figure 9F). By contrast, it failed to block IL1β-mediated suppression of CNT1 (Figure 9E) and ENT2 (Figure 9F) mRNA expression.…”
Section: Resultsmentioning
confidence: 99%